2012
DOI: 10.1088/1741-2560/9/4/046007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of laminin on 3D neurite extension in collagen gels

Abstract: The primary goal of this research was to characterize the effect of laminin on three-dimensional (3D) neurite growth. Gels were formed using type I collagen at concentrations of 0.4-2.0 mg mL(-1) supplemented with laminin at concentrations of 0, 1, 10, or 100 µg mL(-1). When imaged with confocal microscopy, laminin was shown to follow the collagen fibers; however, the addition of laminin had minimal effect on the stiffness of the scaffolds at any concentration of collagen. Individual neurons dissociated from E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 60 publications
(117 reference statements)
0
35
0
Order By: Relevance
“…The addition of laminin did not alter the ultrastructure, because it was expected to coat collagen fibers evenly. Additionally, laminin was also not expected to alter the stiffness/viscoelasticity of the gels, given the manner of its interaction with the collagens [46-48]. The glycosaminoglycan chains of heparan sulfate are documented to cross link between laminin and collagen IV, thereby pulling fibers into a more compact structure, and slightly increasing the viscoelasticity of ECM gels [45, 49].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of laminin did not alter the ultrastructure, because it was expected to coat collagen fibers evenly. Additionally, laminin was also not expected to alter the stiffness/viscoelasticity of the gels, given the manner of its interaction with the collagens [46-48]. The glycosaminoglycan chains of heparan sulfate are documented to cross link between laminin and collagen IV, thereby pulling fibers into a more compact structure, and slightly increasing the viscoelasticity of ECM gels [45, 49].…”
Section: Discussionmentioning
confidence: 99%
“…The most parsimonious explanation is that there exists a feedback mechanism that maintains the overall elongation rate. There are a wide range of factors that can modulate axon growth rate, for example laminin concentration [30,31]. While larger growth cones might sense more laminin, smaller growth cones might compensate with an alteration in integrin expression to sustain a necessary growth rate, as neurons have been shown to vary their expression levels of integrins based on laminin concentration in the substrate [32].…”
Section: Discussionmentioning
confidence: 99%
“…6,32 Functionally, blocking several types of integrins showed that integrins that predominantly bind to laminin were responsible for maintaining the elongated phenotype in Matrigel. This finding is strengthened by the fact that supplementing collagen gels with laminin (in concentrations that were shown to have no influence on the stiffness of the hydrogel 33 ) led to a switch from the blebbing phenotype to the elongated phenotype. Thus, laminin, and not adhesion per se or matrix topography, seems to be crucial in this regard.…”
Section: Discussionmentioning
confidence: 99%